Cress Watercress - Maguire, Gregory; Litchfield, David (2022)
"When Papa doesn't return from a nocturnal honey-gathering expedition, Cress holds out hope, but her mother assumes the worst. It's a dangerous world for rabbits, after all. Mama moves what's left of the Watercress family to the basement unit of the Broken Arms, a run-down apartment oak with a suspect owl landlord, a nosy mouse super, a rowdy family of squirrels, and a pair of songbirds who broadcast everyone's business. Can a dead tree full of annoying neighbors, and no Papa, ever be home?"--
Ages 8-12
Keywords: Rabbits -- Juvenile fiction; Animals -- Juvenile fiction; Families -- Juvenile fiction; Fathers -- Death -- Juvenile fiction; Home -- Juvenile fiction; Animal fiction; Fantasy fiction; Fiction; Juvenile works; Novels; Animal fiction; Fantasy fiction; Novels